Culture and Social Support Seeks It and Why? [article]. - Taylor, Shelley E.
Are Asians and Asian American more or less likely to seek social support for dealing with stress than European Americans? On the one hand, the collectivist orientation of Asian countries might favor the sharing of stressful problems; on the other hand, efforts to maintain group harmony might discourage such efforts. The 2 studies, Koreans (Study 1) and Asians and Asian Americans in the United States (study 2) reported using social support less for coping with stress than European Americans. Study 3 examined potentials explanations for these effects and revealed that relationship concerns accounted for the cultural differences in used of support seeking. Discussion centers on the potential benefits and liabilities of seeking social support. (from the author)